PENGARUH KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA APARATUR SIPIL NEGARA PADA DINAS PEMUDA, OLAHRAGA, DAN PARIWISATA KABUPATEN PASAMAN - Yurasti Yurasti; Rahmi Faura Putri (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2022)
This research were done, in order to determined the effect of ledearship and work discipline on the job performance of civil servants on regional office of Youth, Sports and Tourism of Pasaman Regency. The sample in this study amounted to 51 respondents. The data collected in this study were analyzed using multiple linear regression. The results showed that partially leadership had a significant effect on the job performance of civil servants on Regional Office of Youth, Sports and Tourism of Pasaman Regency, with a significant value of 0.000 < alpha 0.05. Work discipline partially has no significant effect on the job performance of civil servants on Regional Office of Youth, Sports and Tourism Office of Pasaman Regency with a significant value 0.615 > alpha 0.05. Simultaneously leadership and work discipline have a significant effect on the job performance of state civil aparatus at Regional Office of Youth, Sports and tourism of Pasaman Regency, with a significant value 0.000 < alpha 0.05. The results of the coefficient of determination test indicated that leadership and work discipline contribute 51% of job performance of civil servants Keyword: Leadership, Work Discipline, and Job Performance